- STRATEGI KEWIRAUSAHAAN DIGITAL MAHASISWA SISTEM INFORMASI UNIVERSITAS PAMULANG DALAM PEMANFAATAN E-COMMERCE: Pemanfaatan E-Commerce di Universitas Pamulang - Fanni Erda Tasia; Nasmal Hamda; Enok Nurhasanah (Universitas Pasundan, 2025)
The popularity of e-commerce–based entrepreneurship, particularly among university students, has been driven by the rapid development of digital technology. Students of the Information Systems Study Program possess significant potential to create digital businesses by leveraging their information technology knowledge. This study aims to examine the digital entrepreneurship strategies of students at Universitas Pamulang who utilize e-commerce in their business activities. The research involved 23 morning-class students who act as initiators or owners of e-commerce–based businesses. A descriptive qualitative research methodology was employed. Data were collected through observation, documentation, and in-depth interviews. Data analysis was conducted using the interactive model proposed by Miles and Huberman. The findings indicate that students primarily use online marketplaces and social media as their main business platforms. They implement digital marketing strategies through original content creation and online promotions. Despite facing challenges such as limited capital, time management issues, and market competition, their background in information systems supports them in managing digital businesses effectively. This study highlights the importance of digital entrepreneurship strategies and institutional support in assisting students to become successful entrepreneurs.